Techno-Economic and Environmental Assessment of Hydrothermal Carbonization Coupled with Anaerobic Digestion for Sewage Sludge and Municipal Solid Waste Co-Treatment in Chile - Pages-Diaz, J (Elsevier Ltd, 2025)
This work aimed to compare the stand-alone hydrothermal carbonization process (HTC) coupled with anaerobic digestion (AD) for the treatment of HTC-process water in terms of technical, economic, and environmental performance. Three scenarios were evaluated: (i) Stand-alone HTC, (ii) HTC integrated with AD (HTC + AD_1), and (iii) HTC integrated with an improved AD that uses hydrochar (HTC + AD_2). The industrial process was designed and modeled based on experimental data previously obtained for the co-treatment of the organic fraction of municipal solid waste and sewage sludge. The results show that net thermal energy (HTC = 53 kWh/traw material, HTC + AD_1 = 120 kWh/traw material, HTC + AD_2 = 84 kWh/traw material) and net electrical energy (HTC = 149 kWh/traw material, HTC + AD_1 = 187 kWh/traw material, HTC + AD_2 = 187 kWh/traw material) increased in the integrated scenarios by up to 126 % and 26 % respectively, compared to the stand-alone HTC due to extra energy from biogas. Nevertheless, the increase in methane production (58 vs. 153 NmLCH4/gVS) owing to the hydrochar addition did not supply the contribution of direct hydrochar combustion in power plants. Compared to the stand-alone HTC, the waste treatment cost with the cogeneration unit increased by 62 % due to the annexed AD plant. The total annualized cost ranges from 101 (HTC) to 127 (HTC + AD_1) USD/traw material, which is expected to decrease in all scenarios (up to 31 USD/traw material) by increasing the plant capacity (up to 100,000 t/year). The integrated configurations reduce the total environmental impact points (up to 85 %) compared to the stand-alone HTC due to the valorization of the HTC-process water and the replacement of coal fuel. © 2025 Elsevier Ltd